If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3=x-5/6
We move all terms to the left:
-3-(x-5/6)=0
We add all the numbers together, and all the variables
-(+x-5/6)-3=0
We get rid of parentheses
-x-3+5/6=0
We multiply all the terms by the denominator
-x*6+5-3*6=0
We add all the numbers together, and all the variables
-x*6-13=0
Wy multiply elements
-6x-13=0
We move all terms containing x to the left, all other terms to the right
-6x=13
x=13/-6
x=-2+1/6
| 4p+3=3(p-2) | | -3/4x+1/4=13/4 | | -7g-5=8+3g-2 | | 1/3.x=20 | | -4w-11=18 | | 3x+5x+4-x+8=88 | | 3(w-3)-4=-2(-8w+2)-7w | | x-8/11=-2 | | 2(6x-8)=40+4x | | -5+4n+n=2n+15 | | -9=3w+4(w+3) | | -5g(-1)(8-g)=12 | | 7q-9=40 | | 18=5u+2(u-5) | | -61-15x=1-20x+38 | | 5x+8+3x+4=-40+ | | 39=6v+3(v+4) | | 6x-17=3x+40 | | 4=-2r | | 39=6v+3(v=4) | | 5x-2(x-5)=-8+5x+10 | | -14x+132=26(x-18) | | x^2-29x+154=0 | | 6x17=3x+40 | | 0.5(4x-8)+3x=36 | | 29+3x=86 | | 2(6w+8w+6*8)=208 | | 7(0.8t-0.2)=5.2t-1.58 | | 4+13x=14x-4 | | 4x+8x=63 | | 11-24x=-26x-16-5 | | 5+b/4=31 |